PENGARUH KONSENTRASI PROTEIN IKAN LELE TERHADAP KANDUNGAN KIMIA DAN ORGANOLEPTIK KERUPUK IKAN - Rahmi AM Fitrawati; Muhamad Musbah; Muliadin Muliadin; Roni Hermawan; Renol Renol; Mohammad Akbar (Jurnal Pengolahan Pangan, 2018)
Catfish is one of potential fisheries products in Central Sulawesi, but this fact is not in line with community consumption level. Catfishes contain protein and fatty acid which are good for health. The use of catfishes as fish chips become one of the way out to increase the community consumption level. This research aims at knowing the effect of catfishes protein concentration toward chemical content (water content, ash content) and organoleptics. The research result shows that the treatment of catfishes protein concentration is unsignifficantly effect the water and ash content, besides the result of hedonic test shows that the concentration signifficantly effect the taste, the smell and the texture of catfish chips but unsignifficanly effect the colour of it. The treatment by adding 200 g of catfish was being the panels’ most favorite treatment with a score of 4.5 or with the rounding 5 indicated as favored.